1977
DOI: 10.1007/bf01920187
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction and fetal development

Abstract: The effect of deficient nutrition of pregnant Wistar rats on the fetal weight has been studied. It has been established that the fetal weight of the group of rats fed with a restricted amount of stock diet lags behind the fetal weight of the group receiving unrestricted amounts of the same stock diet. The differences in weight between the 2 groups were, on each day of the observation period, significant at the level of p less than 0.05 and p less than 0.01, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The question of whether maternal nutrition has an important influence on fetal growth is not new. There is abundant evidence from wartime studies and their follow-up (Smith, 1947;Antonov, 1947;Stein et al, 1975), animal experiments (Everitt, 1964;Durst-Zivkovic, 1977) and recent work in Guatamela (Lechtig el al, 1975) that maternal undernutrition is n A associated with lower birth weight. The Guatemalan studies have shown that food supplementation not only led to increased birth weight but better long term intellectual performance (Klein et al, 1976).…”
Section: Nutritional Supplementation In Pregnancymentioning
confidence: 99%
“…The question of whether maternal nutrition has an important influence on fetal growth is not new. There is abundant evidence from wartime studies and their follow-up (Smith, 1947;Antonov, 1947;Stein et al, 1975), animal experiments (Everitt, 1964;Durst-Zivkovic, 1977) and recent work in Guatamela (Lechtig el al, 1975) that maternal undernutrition is n A associated with lower birth weight. The Guatemalan studies have shown that food supplementation not only led to increased birth weight but better long term intellectual performance (Klein et al, 1976).…”
Section: Nutritional Supplementation In Pregnancymentioning
confidence: 99%
“…Dietary restriction of 50 %in rats during pregnancy only resulted in significantly reduced foetal weights on days 17-22 of gestation (Durst-Zivkovic 1977).…”
Section: Introductionmentioning
confidence: 99%